Intra-articular biomaterials-assisted delivery to treat temporomandibular joint disorders. (10th May 2018) - Dashnyam, Khandmaa; Lee, Jung-Hwan; Mandakhbayar, Nandin; Jin, Guang-Zhen; Lee, Hae-Hyoung; Kim, Hae-Won
The temporomandibular joint disorder, also known as myofascial pain syndrome, is considered one of the prevalent chronic pain diseases caused by muscle inflammation and cartilage degradation in head and neck, and thus influences even biopsychosocial conditions in a lifetime. There are several current treatment methodologies relieving inflammation and preventing degradation of the joint complex. One of the promising non-surgical treatment methods is an intra-articular injection of drugs such as corticosteroids, analgesics, and anti-depressants. However, the side effects of drugs due to frequent injections and over-doses, including dizziness, dry mouth, and possible drug dependency are considered limitations. Thus, the delivery of therapeutic molecules through the use of nano/microparticles is currently considered as a promising strategy primarily due to the controlled release. This review highlights the nano/microparticle systems for effective intra-articular therapeutics delivery to prevent cartilage degradation and protect subchondral bone in a temporomandibular joint.